Problematika Anak Putus Sekolah Di Gampong Kandang Kecamatan Sakti Kabupaten Pidie - Cut Faizatul Amira (JAROW: Journal of Ar-Raniry on Social Work, 2025)
The case of children dropping out of school is one of the factors that is very seriously handled for the future of the nation. The phenomenon of children dropping out of high school in Gampong Kandang certainly has its own impact, where the child has the potential to be hampered in the level of independence, and there is no increase in competitiveness for children when they are in the community. This study aims to determine what factors cause children to drop out of school and to determine what socio-economic characteristics cause children to drop out of school in Gampong Kandang, Sakti District, Pidie Regency. This research method uses a qualitative approach with a descriptive research type. Data collection techniques are carried out by interviews, observation and documentation. The results of the study showed that the cause of children dropping out of school in Gampong Kandang is an internal factor (interest and desire), this factor occurs in the child concerned himself which is caused by the absence of intention or desire to learn. Meanwhile, internal factors are caused by the economic limitations of parents, because the parents' income is insufficient or only enough for daily needs, so that parents are unable to facilitate children to go to school, and the social environment due to free association, the influence of peers. Lack of parental supervision is often the reason why children are lazy to study and prefer the freedom to do whatever they want with their friends.